Taxonomy and distribution of the Pygmy Eagle Aquila (Hieraaetus) weiskei (Accipitriformes: Accipitridae) - Gjershaug, Jan O.; Lerner, Heather R. L.; Diserud, Ola H. (Zootaxa, 2009)
We re-evaluated the taxonomic status of the New Guinean subspecies weiskei of the Little Eagle Aquila morphnoides and confirmed that it differs considerably from the Australian A. morphnoides in multiple morphological and plumage characters. Genetic differentiation in published mitochondrial cyt-b and ND2 sequences between the nominate subspecies and weiskei is equivalent to that found between other accipitrid taxa at the species level, as are pairwise divergences between each Little Eagle taxon and their sister species, the Booted Eagle A. pennata. The available morphological and genetic evidence thus strongly and unambiguously supports the specific distinctness of A. weiskei. We propose the English name Pygmy Eagle, as this is the world’s smallest known eagle. We show that the distribution of A. weiskei includes the western part of New Guinea (Vogelkop) and the Moluccas (Halmahera, Ternate and Seram), based on our new observations.